The Effects of Customer Incivility Experience and Job Satisfaction on the Happiness of Employees: A Moderated Mediation Model of Appearance Satisfaction - Byung Soo Chang, Eun Ju Jang (International Journal of Advanced Science and Technology, 2020)
Background/Objective: The purpose of this study was to verify the moderated mediation effect of appearance satisfaction in the influence of customer incivility experience and job satisfaction on happiness by surveying 222 employees working at highway rest stops in Korea.